2015
DOI: 10.1890/es14-00155.1
|View full text |Cite
|
Sign up to set email alerts
|

Hog badger (Arctonyx collaris) latrine use in relation to food abundance: evidence of the scarce factor paradox

Abstract: 2015. Hog badger (Arctonyx collaris) latrine use in relation to food abundance: evidence of the scarce factor paradox.Ecosphere 6(1):19. http://dx.doi.org/10.1890/ES14-00155.1Abstract. Many carnivores use latrines, and investigations of latrine use have typically been concerned with territorial defense, often at the expense of fully evaluating other, not mutually exclusive, functions. In particular, the relationship between food abundance and latrine use patterns has been explored inadequately, where latrine l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…In contrast, Stamps and Buechner () suggested that the maintenance of border latrines might aid in the defense of food resources, which has been proposed as the main latrine function also in the more solitary hog badger Arctonyx collaris (Zhou et al. ). Roper et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Stamps and Buechner () suggested that the maintenance of border latrines might aid in the defense of food resources, which has been proposed as the main latrine function also in the more solitary hog badger Arctonyx collaris (Zhou et al. ). Roper et al.…”
Section: Discussionmentioning
confidence: 99%
“…Kilshaw et al (2009) observed that badgers often defecated along a different border stretch than that closest to their current feeding areas, and interpreted this as evidence for a division of labor in border marking. In contrast, Stamps and Buechner (1985) suggested that the maintenance of border latrines might aid in the defense of food resources, which has been proposed as the main latrine function also in the more solitary hog badger Arctonyx collaris (Zhou et al 2015). Roper et al (1986) suggest that range exclusivity maintained by borderlatrine marking may serve in mate defense (antikleptogamy hypothesis); nevertheless, recent genetic evidence has revealed a promiscuous, polygynandrous mating system with high rates of extra-group paternity in high-density badger populations (Woodchester Park: Carpenter et al 2005, Wytham Woods: Dugdale et al 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Information on the status of these three species in the wild is very limited (Zhang et al 2009;Zhou et al 2013Zhou et al , 2015a, frustrating efforts to evaluate the impact of this illegal exploitation in the region. We exemplify here how applying genetic monitoring techniques to sample confiscated specimens can provide a useful tool to study the status and sustainability of wild populations (Dawnay et al 2008;DeMATTEO et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…O'Mahony et al 2006), and for other generalist mustelids as well (e.g. Zhou et al 2015aZhou et al , 2015b. We were confident in this technique, assisted by an expert marten hunter (coauthor Evgeniy Raichev), and did not feel that recourse to genetic methods was necessary for this study (see Davison et al 2002).…”
Section: Sample Collectionmentioning
confidence: 93%